2011
DOI: 10.1016/j.taap.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and arsenic methylation efficiency in adult women from southwest U.S. and northwest Mexico

Abstract: Human arsenic methylation efficiency has been consistently associated with arsenic-induced disease risk. Interindividual variation in arsenic methylation profiles is commonly observed in exposed populations, and great effort has been put into the study of potential determinants of this variability. Among the factors that have been evaluated, body mass index (BMI) has not been consistently associated with arsenic methylation efficiency, however an underrepresentation of the upper BMI distribution was commonly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 47 publications
6
53
0
1
Order By: Relevance
“…Some authors (Tseng et al, 2005;Ahsan et al, 2007;Huang et al, 2007;Lindberg et al, 2007;Gomez-Rubio et al, 2011) reported that the subjects with a higher BMI showed an increased percentage of DMA excretion and a reduced percentage of MMA and iAs. Conversely, a small number of studies have shown an inverse direction or no association between BMI and arsenic methylation efficiency (Li et al, 2008;Lindberg et al, 2008).…”
Section: Groupsmentioning
confidence: 99%
“…Some authors (Tseng et al, 2005;Ahsan et al, 2007;Huang et al, 2007;Lindberg et al, 2007;Gomez-Rubio et al, 2011) reported that the subjects with a higher BMI showed an increased percentage of DMA excretion and a reduced percentage of MMA and iAs. Conversely, a small number of studies have shown an inverse direction or no association between BMI and arsenic methylation efficiency (Li et al, 2008;Lindberg et al, 2008).…”
Section: Groupsmentioning
confidence: 99%
“…A study conducted in a female population in southwest Arizona and northern Mexico determined a positive correlation between arsenic methylation efficiency and body mass index (Gomez-Rubio et al, 2011). Specifically, a lower MMA coupled to a higher DMA/MMA ratio was measured in the urine of these women.…”
Section: Discussionmentioning
confidence: 99%
“…So a more conservative analysis was performed that has been used in past studies when urine samples were collected and stored over a substantial period of time [13]. The metabolites of inorganic As in urine [inorganic As (III), methylarsonic acid (MMA) (V), dimethylarsinic acid (DMA), inorganic As (V), and AsB, in ppb] were determined using inductively coupled plasma mass spectrometry [14].…”
Section: Methodsmentioning
confidence: 99%